2016
DOI: 10.5812/numonthly.31108
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and Complications of Removing Ureteral Stent Based on the Elapsed Time After Renal Transplantation Surgery

Abstract: BackgroundThe most important surgical complications of renal transplantation are stenosis and obstruction of anastomosis of the ureter to the bladder. Although the routine use of the ureteral stents to prevent such complications seems rational, the optimal time to keep the ureteral stent is still controversial.ObjectivesThis study presents the benefits and complications of removing the ureteral stent based on the elapsed time after the surgery.Patients and MethodsAll patients who underwent kidney transplantati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 3 publications
0
13
0
3
Order By: Relevance
“…Of the 1043 articles identified from the initial literature search, fourteen articles were within the scope of this systematic review; three randomised controlled trials (RCTs) [20,21,31], nine retrospective cohort studies [8,13,19,22,23,32,33,34,35] and two prospective studies [36,37]. A total of 3216 patients were included, of which 2406 patients (74.8%) underwent living donor KTx (two studies did not record if they used living or deceased donors [34,35]).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the 1043 articles identified from the initial literature search, fourteen articles were within the scope of this systematic review; three randomised controlled trials (RCTs) [20,21,31], nine retrospective cohort studies [8,13,19,22,23,32,33,34,35] and two prospective studies [36,37]. A total of 3216 patients were included, of which 2406 patients (74.8%) underwent living donor KTx (two studies did not record if they used living or deceased donors [34,35]).…”
Section: Resultsmentioning
confidence: 99%
“…We could not specify the type of stent in five studies. The authors of these five papers were contacted, but unfortunately, we received no response [19,34,35,36,37]. All studies reported the age of the recipients, except for the preliminary results in the three included abstracts [34,35,36].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations